Buddhism and Christianity in Japan: From Conflict to Dialogue, 1854-1899 - Tucker, B D (Japanese religions, 1988)
Review of Thelle, Notto R. Buddhism and Christianity in Japan: From Conflict to Dialogue, 1854-1899. Publisher: Honolulu : Univ of Hawaii Pr, 1987.